Moose als Indikatoren von Klimafluktuationen in Mitteleuropa - Frahm, Jan-Peter; Klaus, Dieter (ERDKUNDE, 1997)
During the past ten years, several bryophytes with atlantic, atlantic-mediterranean or mediterranean ranges in Europe have spread into continental Europe. Examples are given for 16 species which were found some hundred kilometers east, south-east or north-east of their continuous ranges in this period. Since bryophytes have their main growth period in winter times, it is assumed that these range extensions are a result of mild winters. The extension of bryophyte species with a western distribution in Europe during this period correlates with an increase of the winter temperatures in the past years, an increase of cyclonic activity during the winter months and a reduction of periods with high air pressure. Some bryophyte species seem therefore to be valuable indicators for climatic fluctuations during winter months and can be used for monitoring of climatic fluctuations.